SESAME OIL EXTRACTION AND ANTIOXIDANT ACTIVITY OF LIGNANS FROM LOCALLY CULTIVATED SESAME SEEDS (Sesamum indicum L.) - & Shakir, Shamrad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The present study was designed to evaluate oil extraction from locally cultivated sesame seeds using three extraction methods: soxhlet, cold extraction and batch hydraulic pressing. The soxhlet method was the most effective one. The highest performance value was obtained using n-hx as a solvent in the soxhlet at 60°C/ 6 h. The percentages of oil from unroasted dehulled sesame seeds was significantly higher than those extracted from roasted and unroasted undehulled sesame seeds. Lignans were isolated from roasted and unroasted sesame seeds oil, and the lignans purity was confirmed by analysis. The antioxidant activities of lignans were evaluated by DPPH and reducing power assays. The reducing power activity of lignans from roasted sesame seeds oil (LRSO) was higher than that for the lignans from unroasted sesame seed oil (LURSO), while reducing power activity of BHT as a control was higher than that of LRSO and LRSO. LRSO showed high scavenging radical activity compared to that for BHT and LRSO, due to the presence of sesamol in LRSO which it has strong antioxidant activity.